Oficina de língua inventada e o ensino de conceitos linguísticos - Girardi, Jane Eder (2020)
This dissertation aims to explore the possibility of teaching linguistic concepts by using as a method the creation of a language by speakers. The objective of this research is to verify, initially, what would be the advantages and disadvantages of this possibility. For this, students from the 6th and 7th grades of a public school in the city of São Carlos participated as subjects in the experiment. The experiment was applied in two different groups, with different approaches and activities, so that the results were different. In the first application, the students did not receive any direction to create their fictional language. The results were essential to the consideration of the second part. The part II of this research has been directed in the activities and discussions about languages. Thus, the data from both parts of the research were analyzed and compared, namely: students' language intuitions. We realize from this research that students do not distinguish spoken language from written language, that is, for them, both have the same language system. Therefore, in the second part, the difference between speech and writing was discussed to guide the students regarding language elaboration. Moreover, it was noted that the languages of the first phase were less economical than those of phase II. This is due to the concept that students have about language, because language is synonymous with writing for them, and writing usually assumes that there is some difficulty that encompasses it, because to learn it, it is necessary to master the rules of language cultured standard norm. To dispel this stigma, we tried to show students that every speaker has a language intuition, that the speaker is born with an internalized grammar and that it is possible to understand the linguistic aspects and phenomena about languages. Therefore, it was proposed the activity of creating a language, which aims, at this early stage, only to collect and analyze the data to investigate whether through this activity the student's intuition can emerge.